Pesantren and Takzir in Indonesia: Lawrence Friedman’s Legal System Perspective - Muhammad Chairul Huda; Sukirno Sukirno; Sukron Ma’mun (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
This article explains the legal system existing in the Pesantren, particularly in the term of takzir called perceived as non-human punishment contradictory with human rights. This research took place in Pondok Pesantren Edi Mancoro (PPEM) Salatiga with inclusive and tolerant characters, and voicing religious moderation. PPEM has had alumni becoming national figures. This study employed Lawrence Friedman’s legal system theory requiring the functioning of law in three components: legal structure, legal substance, and legal culture. This research employed qualitative method with data source obtained from field work study with depth interview technique and descriptive interpretive analysis. The result of research showed that Pesantren Edi Mancoro has legal system component as required by Friedman. In the context of takzir, there is a shift in the takzir (punishment) application method to evidently undisciplined students or those committing crime. Takzir contributes to creating personality (noble character) of santri in undertaking life post-pesantren. Takzir actually has educative values not contradictory with human rights. So, takzir in pesantren fulfills all components of legal system suggested by Friedman. Out of the three components, legal culture is the basic components of takzir functioning in pesantren, either internal or external legal culture.